THE CONSTRUCTION OF MORAL VALUES IN THE #STOPCHILDMARRIAGE CAMPAIGN ADVERTISEMENT: A STUDY OF THE INFLUENCE OF PKBI MESSAGES ON PUBLIC PERCEPTION - Setiana, Dinda Nabila (Universitas Mercu Buana, 2025)
Child marriage is a complex social issue that remains a reality in various regions of Indonesia. This phenomenon is driven by multiple factors, including poverty, low levels of education, and strong cultural and social norms. Social campaigns through advertising media have become an important strategy for changing public perceptions regarding child marriage. This study focuses on Roland Barthes’ semiotic analysis of the PKBI #StopChildMarriage campaign advertisement, aiming to reveal how moral values are constructed through systems of signs to deconstruct myths and ideologies underlying the practice of early marriage. Barthes distinguishes three levels of meaning: denotative (literal meaning), connotative (cultural meaning), and myth (ideological meaning). This research employs a qualitative approach, drawing on Barthes’ semiotic analysis. Data were collected by documenting PKBI campaign advertisements and subsequently analyzed to identify the sign structures and the moral messages conveyed. The findings indicate that PKBI’s advertisements not only deliver informative messages but also construct a discourse of resistance against patriarchal values that legitimize child marriage. Through visual and narrative representations, the advertisements aim to raise collective public awareness and normalize new perspectives that support the protection of children’s rights. In conclusion, media campaigns that employ Barthes’ semiotic approach can serve as effective communication tools for conveying moral messages and shaping public opinion on social issues, particularly child marriage